2017
DOI: 10.1016/j.cub.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Paleozoic Nymphal Wing Pads Support Dual Model of Insect Wing Origins

Abstract: The appearance of wings in insects, early in their evolution [1], has been one of the more critical innovations contributing to their extraordinary diversity. Despite the conspicuousness and importance of wings, the origin of these structures has been difficult to resolve and represented one of the "abominable mysteries" in evolutionary biology [2]. More than a century of debate has boiled the matter down to two competing alternatives-one of wings representing an extension of the thoracic notum, the other stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 29 publications
1
38
1
1
Order By: Relevance
“…By adopting the use of tracheation, we do not imply anything regarding wing origins as it relates to the defunct "exite" or "gill hypothesis" for overall wing homology, that is, wings as serial homologs with abdominal gills found in some crown-group naiads (e.g., Landois, 1871;Wigglesworth, 1976;Kukalová-Peck, 1978, 1983, 1991, which is in opposition to the "paranotal hypothesis" (e.g., Müller, 1873aMüller, , 1873bMüller, , 1875Crampton, 1916;Hamilton, 1971Hamilton, , 1972aWootton, 1976;Rasnitsyn, 1981). Instead, wings have been more recently determined to be of largely notal origin with the incorporation of subcoxal elements to form an articulation at the base, also known as the dual model hypothesis (e.g., Grimaldi and Engel, 2005;Niwa et al, 2010;Engel et al, 2013;Prokop et al, 2017). In this context, the tracheae of the wing represent nothing more than similar tracheation of any body structure.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…By adopting the use of tracheation, we do not imply anything regarding wing origins as it relates to the defunct "exite" or "gill hypothesis" for overall wing homology, that is, wings as serial homologs with abdominal gills found in some crown-group naiads (e.g., Landois, 1871;Wigglesworth, 1976;Kukalová-Peck, 1978, 1983, 1991, which is in opposition to the "paranotal hypothesis" (e.g., Müller, 1873aMüller, , 1873bMüller, , 1875Crampton, 1916;Hamilton, 1971Hamilton, , 1972aWootton, 1976;Rasnitsyn, 1981). Instead, wings have been more recently determined to be of largely notal origin with the incorporation of subcoxal elements to form an articulation at the base, also known as the dual model hypothesis (e.g., Grimaldi and Engel, 2005;Niwa et al, 2010;Engel et al, 2013;Prokop et al, 2017). In this context, the tracheae of the wing represent nothing more than similar tracheation of any body structure.…”
Section: Introductionmentioning
confidence: 64%
“…In fact, no extinct or extant taxa are documented in which there are paired stems at each axillary point (i.e., paired stems at the base for each longitudinal vein system). Moreover, recent evidence from the nymphal pads of Palaeodictyoptera (Prokop et al, 2017) tends to support Hamilton's (1972a) hypothesis regarding the groundplan venation for insect wings, one that does not include paired, basal stems.…”
Section: The Controversy Of 'Ma'mentioning
confidence: 91%
See 1 more Smart Citation
“…While we were revising this manuscript, Prokop et al reported very intriguing findings that provide support for a dual origin of insect wings from the paleoentomological point of view 59 . Collaboration among various fields, including paleontology and evo-devo, will be fruitful to tackle this century-old question regarding the evolutionary origin of insect wings.…”
Section: Note Added In Revisionmentioning
confidence: 85%
“…The model design imitating insect membranous wings has practical significance. The insect species is more and the forms of membranous wings are complicated and varied, which provides abundant natural sources for the research on biomimetic thin-film materials and biomimetic 2-dimensional composite materials [8, 9]. There are many factors affecting the model imitating insect membranous wings, such as the material property of veins and membranes, distribution and quantity of veins, and appearance of membranous wings [10–12].…”
Section: Introductionmentioning
confidence: 99%